The Principal's Role in Improving the Professionalism of Early Childhood Education Teachers at KB - TK Islam Al Azhar 29 BSB Semarang (PIAUD IAIN Kudus, 2025)
Professional teachers have strong knowledge, commitment to students' needs, high moral awareness, and a strong individual and collective identity. Every student in PAUD deserves proper support and care from parents and teachers to get appropriate educational stimulation. This study aims to analyze the role of the principal in improving the professionalism of PAUD teachers at KB-TK Islam Al Azhar 29 BSB Semarang. This type of research is descriptive qualitative research collecting data through observation and in-depth interviews. The principal and other teachers are the research subjects. The results showed that principals play an important role in improving teachers' professionalism through various strategies, such as training, academic supervision, discussion forums, and periodic performance evaluations. In addition, principals create a supportive educational environment through progressive school policies and collaboration with the foundation to improve teachers' competencies. This study concludes that the active role of school principals in facilitating teachers' professional development is critical to creating a quality learning environment and supporting the growth of ECD learners. The implications of this study emphasize the need for continuous support from school stakeholders in improving ECD teachers' competencies and performance on an ongoing basis